Contamination and ecological risk assessment of trace metals in surface sediments from coastal areas (El Jadida, Safi and Essaouira) along the Atlantic coast of Morocco. (February 2022) - Kouali, Hassnae; Chaouti, Abdellatif; Achtak, Hafid; Elkalay, Khalid; Dahbi, Abdallah
Abstract: Concentrations of four trace metals (Cd, Cr, Cu and Zn) in surface sediments were quantified seasonally to evaluate the metal contamination and to determine the possible environmental risks at three coastal areas in northwest Morocco (El Jadida, Safi and Essaouira). Sampling was conducted quarterly at six intertidal stations with two stations per area (north to south: El Jadida: S1 vs. S2; Safi: S3 vs. S4 and Essaouira: S5 vs. S6). The trace metal concentrations were generally found to be greater in wet seasons for all sampling stations, and their mean values were arranged in the following decreasing order: Zn (28.35–136.10 μg g −1 dry weight) > Cr (6.50–130.90 μg g −1 ) > Cu (5.00–83.40 μg g −1 ) > Cd (0.02–5.95 μg g −1 ). As expected, the highest metal concentrations were recorded at stations exposed to the polluting point-source discharges from important industrial phosphate plants near El Jadida (S2-Jorf Lasfar) and Safi (S4-Jorf Lihoudi), which greatly exceeded the geochemical background values (Cd: 0.3 μg g −1 dry weight, Cr: 90 μg g −1, Cu: 45 μg g −1 and Zn: 95 μg g −1 ). All of the four trace metals were significantly correlated with each other, implying the same source of contamination and a similar pollution history. This was mainly derived from industrial waste generated by these huge phosphate industry plants. Meanwhile, results from hierarchical cluster analysis confirmed the findings from the correlations. This ecotoxicological evidence was primarily associated with untreated industrial discharge. The contamination Factor, degree of Contamination, and modified Degree of Contamination indices confirmed that these two stations were the metal contamination hotspots, and the most affected in this region, especially for Cd. Moreover, Pollution Load Index and Geo-accumulation Index reflected a spatial distribution of pollution following the decreasing sequence S4 > S2 > S1 > S6 > S3 > S5. Based on the Potential Ecological Risk Index, Cd concentrations indicated a moderate to very high potential ecological risk at all sampling stations, except at one pristine station S5 (Bhibeh). The spatial distribution of Mean-Effect Range Median-Quotient (M-ERM-Q) showed a negligible ecological risk at Cap Beddouza (S3) and Bhibeh. The mean values of Toxic Units (Σ TU) were found in the following decreasing order Cd > Cu > Cr > Zn, with a major contribution to the Σ TU coming from Cd (35.42%) and Cu (24.99%). Comparison of the current results with those found in other areas around the world revealed that the metal levels obtained here are in general low, except for Cd, which appeared to be in higher concentrations. Concentrations of Cd, Cr and Cu in sediments at S2 and S4 exceeded either the Threshold Effect Level of the Canadian sediment quality guidelines and Effect Range Low of the US National Oceanic and Atmospheric Administration, which demonstrated that these trace elements posed environmental risks while Zn appeared to present no environmental threat at all of the studied areas. Graphical abstract: Image 1 Highlights: The trace metal distribution showed seasonal patterns with elevated concentrations in winter. The greatest metal concentrations were recorded at stations exposed to the polluting phosphate industry discharges. The metal accumulation in sediments was derived from the same contamination sources. The elevated ecological risk in the heavily industrialized stations should be of concern for marine life and human health. The presumed non-contaminated locations are no longer likely to be considered as control stations in the future.